Identifying Critical Patient Safety Dimensions and the Impact of Culture on Nurse Turnover - Abdulrahman Saleem Almalki,; Amal Hamad Mohammad Alhassoon,; Ahmed Juwaybir Onayz Alsulami,; Mazen Hamdan Salem Altalhi,; Alanazi Yazeed Atallah B,; Majed Hamoud Alotaibi,; Fatemah Hussain Ali Hothan,; Fahad Saeed Burayz Almutairi,; Abdullah Saleh Abdullah Alhujaylan,; Kayed Farah Al Otaibi,; Khalid Mihmas Aljish,; Bander Barak Saud Alotabi, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The primary threat to patient safety is a lack of understanding of the causes of nurse turnover, which directly impacts the care provided by staff in accordance with the patient safety culture (PSC). Identifying key factors influencing nurse turnover is crucial. Aim of the study : it assess the l critical patient safety culture dimension and its relationship with nurses turnover at KSA Method Research design: Descriptive cross sectional research design was utilized to conduct this research Setting:The study was conducted in the largest five Hospitals Dammam, Saudi Arabia . Participants :All healthcare workers actively nurses in the largest five Hospitals Dammam . 290 out of 350 nurses of the five hospitals participating facilities received a self-administered survey through a special email link over the course of two weeks in February and March of 2024.a convenience sampling method was used to recruit nurses Informed consent was acquired, and participation in the survey was anonymous and voluntary. Out of an estimated 350 nurses professionals working across the facilities, 290 completed surveys were returned, resulting in an 88.5% response rate. Study questionnaire: Patient Safety Culture and Attitudes Questionnaire. to assess the patient safety culture in hospital. Intention to Stay Questionnaire (ISQ) to measure nurses intentions to stay with the organizationData collection: The researcher approached selected nurses during breaks with hand-delivered questionnaires. Before distributing the questionnaire, the researcher stated the study's purpose and provided any necessary instructions. Results:The perception of patient safety culture has a percentage score of 56.80 ± 14.83. The most significant subscale was perception of the unit's patient safety culture (mean ± SD = 59.95 ± 15.20), followed by communication (mean ± SD = 53.02 ± 19.53). The supervisor/manager subscale had the lowest mean ± SD (48.31 ± 19.86). Table 2 shows that more than half (53.1%) of the nurses polled had a moderate inclination to stay.Also, there is a somewhat negative correlation (r = -0.32, p = 0.015) between patient safety culture and anticipated turnover (19.86). Conclusion:This study adds to the previous literature by highlighting the link between patient safety culture and intent to depart. Improving patient safety culture can increase nurses' retention and reduce turnover, according to the findings. Fostering a patient-safety culture through strong leadership is vital for retaining nurses.